Migrant Networks and Destination Choice: Evidence from Moves across Turkish Provinces - Abdurrahman Aydemir; Erkan Duman (Institute of Labor Economics (IZA), 2021)
This paper estimates effects of birth place migration networks and other location attributes on destination choices of internal migrants conditional on migration. We also study heterogeneity in the role of these factors for migrant types who differ by skill group, age at migration, and reason of migration. We use data on male migrants from three rounds of Turkish censuses 1985, 1990 and 2000 who choose among 67 provinces. We find that migrants are drawn to provinces with larger networks, relatively better economic conditions, and distance is a significant deterrent for migration. There are, however, significant heterogeneities across migrant types. More educated move longer distances and rely less on networks for destination choice. Importance of labor market conditions increases and the effect of distance decreases with age. Among migrants with different reason of migration, labor market conditions play a significant role only for migrants moving for employment reasons and networks matter less for this group.
Keywords: J61; O15; R23; Z13; 330; migration; networks; destination choice; education; reason of migration; heterogeneous effects